Voltage profile enhancement in distribution network using static synchronous compensator STATCOM - Mohammed Yahya Suliman (International Journal of Electrical and Computer Engineering (IJECE), 2020)
STATCOM is one of FACTS devices that used as regulator for transmission and distribution systems which works for reactive power compensation. STATCOM utilisation in distribution system mostly for enhancing the profile of voltage, where used for adjusting the disturbance voltage by injecting into the system a controllable voltage. This paper present a Fuzzy controller based on STATCOM to enhance the voltage profile in distribution network. The controller of STATCOM has simulated for different types of abnormal load conditions of balance and unbalance load. The results of simulation show ability of proposed design to enhance the load voltage which was 96% of the nominal value.